Digital technology in medical visits: a critical review of its impact on doctor-patient communication - Marino, Filomena; Alby, Francesca; Zucchermaglio, Cristina; Fatigante, Marilena (Frontiers in Psychiatry, 2023)
With the rapid advances of digital technology, computer-mediated medical practices are becoming increasingly dominant in medical visits. However, the question of how to ensure effective, patient-centered communication in this transition remains crucial. In this mini-review, we explore this topic by reviewing quantitative and survey-based studies, as well as discursive-interactional studies that focus on the visit as a communicative event. The review is organized into four sections: the introductory section provides a brief synthesis of the two main models used in medical practice and describes the effects of patient-centered communication practices on patients’ health and well-being. The second section presents and discusses qualitative and quantitative studies that assess the effect of technology on medical interaction and its impact on patient-centered communication. The third section focuses on whether and how the digital medical record represents a “potential communication risk” during doctor-patient interactions and explores how certain pen-and-paper literacy practices could help mitigate these challenges. In the concluding section, we outline and analyze three key considerations for utilizing technologies to foster and enhance patient-centered communication during medical visits.